Contemporary refugee and forced migrants issues: an analysis in the context of legal framework (International relations and international law Journal, 2018)
Global mobility has become one of the important and revealing trends in the current international relations and law. Forced migrants’ and refugees’ issues come from the past, but their solution is urgently needed now. This issue acquires particular significance and multidimensionality in the modern context of globalization and the intensification of conflicts in all regions of the world. Other factors, such as natural disasters and economic crises, are also sources of forced mobility. The volumes of forced migration and the flow of refugees have acquired immense proportions and consequences in the current context. The main contribution to the solution of the problem was made by the United Nations Organization and UNHCR, its specialized agency. Key documents were also developed and adopted within and with the support of this structure. Presently there is a robust set of legal instruments for the coordination and advocacy of migration processes, but new approaches are urgently in need because of changing patterns in migrant movements. Moreover, the insufficiency in the definition of persecution, which excludes many categories of contemporary migrants, has only increased the need for the adoption of new Global Compacts within the framework of the UN. Hence, this paper looks into the urgent need for rethinking on theoretical approaches, including conceptual apparatus, legal aspects and some practical approaches to the participation of the entire international community.Key words: Migration Issues and International Law, Refugees, Forced Migration, UNHCR.